Accuracy of self‐reported and measured anthropometric data in the inpatient population. Issue 6 (24th April 2014) - Babiarczyk, Beata; Sternal, Danuta
Abstract : Self‐reported body mass index (BMI) is commonly used to assess nutritional status. The aim of the study was to assess the accuracy of self‐reported and measured data obtained from the inpatient population. A total of 296 individuals admitted to five hospital wards were included in the study. Patients provided details of their height and weight, and measurements of height and weight were subsequently taken. BMI measurements were calculated from both the self‐reported and the measured data. In general, the study participants overestimated their height and underestimated their weight. Older people and women were significantly more likely to overestimate their height, whereas better educated people were more likely to underestimate their weight. Inaccurate height and weight reporting led to BMI values being underestimated. The findings of this study support previously published research questioning the accuracy of self‐reported height and weight measurements.